2021
DOI: 10.1101/2021.06.14.21258569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subcutaneous REGEN-COV Antibody Combination in Early Asymptomatic SARS-CoV-2 Infection: A Randomized Clinical Trial

Abstract: Background: Casirivimab and imdevimab administered together (REGEN-COV) markedly reduces the risk of hospitalization or death in high-risk, symptomatic individuals with COVID-19. Here, we report phase 3 results of early treatment of asymptomatic, SARS-CoV-2-positive adults and adolescents with subcutaneous REGEN-COV. Methods: Individuals ≥12 years of age were eligible if identified within 96 hours of a household contact being diagnosed as SARS-CoV-2-positive; 314 were randomized 1:1 to receive subcutaneous RE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…After screening 52350 titles and abstracts and 1029 full texts, 47 unique randomised controlled trials that evaluated antiviral antibody or cellular treatments were identified as of 21 July 2021 (fig 1). 43444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788 A table of excluded full texts is provided in the supplementary data on bmj.com. Searches of living evidence retrieval services identified 11 publications of eligible randomised trials, which were reconciled with our formal search strategy when necessary 222324254549566466676875838688.…”
Section: Resultsmentioning
confidence: 99%
“…After screening 52350 titles and abstracts and 1029 full texts, 47 unique randomised controlled trials that evaluated antiviral antibody or cellular treatments were identified as of 21 July 2021 (fig 1). 43444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788 A table of excluded full texts is provided in the supplementary data on bmj.com. Searches of living evidence retrieval services identified 11 publications of eligible randomised trials, which were reconciled with our formal search strategy when necessary 222324254549566466676875838688.…”
Section: Resultsmentioning
confidence: 99%
“…An ongoing randomized, double-blind, placebo-controlled, phase 3 trial (NCT04452318) is assessing the efficacy of subcutaneous casirivimab/imdevimab in preventing SARS-CoV-2 infection and subsequent symptomatic COVID-19 in uninfected household contacts of infected individuals (part A) and preventing symptomatic COVID-19 in household contacts recently infected with SARS-CoV-2 but asymptomatic (part B) [ 9 , 20 , 21 ]. The trial enrolled individuals aged ≥ 12 years living with a SARS-CoV-2-infected patient.…”
Section: Scientific Summarymentioning
confidence: 99%
“…In cohort B, early treatment with casirivimab/imdevimab was effective in preventing asymptomatic SARS-CoV-2 infection from progressing to symptomatic COVID-19 [ 20 ]. Of the 314 subjects randomized in this cohort, 207 were seronegative at baseline and 204 of these were assessed for efficacy (three seronegative subjects were determined post-randomization to be symptomatic at baseline and excluded).…”
Section: Scientific Summarymentioning
confidence: 99%
See 2 more Smart Citations